2017
DOI: 10.5751/es-08990-220119
|View full text |Cite
|
Sign up to set email alerts
|

A life course approach to understanding social drivers of rangeland conversion

Abstract: ABSTRACT. Grassland to woodland conversion, also known as woody plant encroachment (WPE), is a global-scale phenomena caused in large part by changes in social processes that affect rural land use patterns. Woody plant encroachment has raised serious concerns for species conservation, provision of ecosystem services, and viability of rural livelihoods and cultures. We examined the social drivers of WPE using a case study of rangelands in a semi-arid watershed. We employed the life course framework to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Our results indicated that landownership motivations are significant drivers of woody cover preference, a finding corroborated by others [ 23 , 24 ]. Those who owned their property for recreation or hunting preferred more woody plant cover while more traditional livestock-oriented ranchers preferred less.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results indicated that landownership motivations are significant drivers of woody cover preference, a finding corroborated by others [ 23 , 24 ]. Those who owned their property for recreation or hunting preferred more woody plant cover while more traditional livestock-oriented ranchers preferred less.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found significant inter-state differences in woody cover preferences, with Texas respondents generally preferring higher cover (25%) compared to their Oklahoma counterparts (5%). In part, the preference for more woody cover among Texas respondents may be due to the marked increase in Central Texas of landowners who are moving away from traditional farming and ranching into recreational or wildlife-centric land uses [23,24]. By contrast, the lower woody cover preference in Oklahoma may be attributable to the continued importance of the ranching industry, particularly cattle ranching [25].…”
Section: Plos Onementioning
confidence: 99%
“…Societal developments like remote work, decreased transportation costs, expansion of digital and service-oriented industries, and the romanticization of rural life draw newcomers to rural areas (Jackson-Smith 2003 ; Gosnell and Abrams 2011 ). Other forces drive residents away from rural areas, such as government regulations and societal hostility to ranching (Liffmann et al 2000 ; Hurst et al 2017 ). Landownership change is also driven by loss of intergenerational succession, influenced by political and financial factors like accessibility of grazing allotments, state and federal tax codes, land use planning, and incentive programs like conservation easements (Brunson and Huntsinger 2008 ; Haggerty et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cessation of fire has affected vegetation composition and wildlife use of grasslands throughout the study area (Kirsch and Kruse 1973) and beyond. In order to maintain grassland integrity globally, we need a focused effort to characterize and address how human perceptions of fire and the effects of prescribed fire management are affecting human prescribed fire management decisions (Gobster et al 2016, Hurst et al 2017, including decisions surrounding the seasonality, frequency, and intensity of prescribed fire management.…”
Section: Discussionmentioning
confidence: 99%